They acclaimed, I used: an investigation of traveller’s behavioural intention to use YouTube shorts for selection of ecotourism destination - Sharma, Nidhi; Arora, Nilesh (Emerald Publishing Limited, 2024)
Purpose: Social media offers better prospect for travellers to seek for travel information, choose a location and share their personal travel experiences. The current study aims to examine how tourists gather information from YouTube shorts and its influence on their intention to use it for selection of an ecotourism destination. Design/methodology/approach: The conceptual model of the study is constructed on information adoption model (IAM). An adaptive questionnaire was utilised to gather 374 valid responses. Partial least square structural equational modelling (PLS-SEM) was utilised for data analysis. Findings: The results showed a positive significant relationship between all the constructs of IAM. The findings also show significant mediating effect of attitude and moderating effect of involvement between information quality and adoption also between source credibility and information usefulness. Research limitations/implications: This study will help destination marketers by providing valuable insights to them to promote their destinations more effectively on social media platforms. This study will also help travel influencers in understanding what are the factors they should focus on while providing information about ecotourism destination. It will additionally help the local economy and conveys a message to travellers about responsible travel behaviour when selecting or visiting ecotourism destination. Originality/value: This is the very first attempt to investigate the adoption of YouTube shorts information and formulating behavioural intentions to utilise it for ecotourism destination selection.